Influence of the introduction of caseload requirements on indication for visceral cancer surgery in Switzerland. Issue 6 (June 2021) - Kaech, Max; Deutschmann, Elisabeth; Moffa, Giusi; Haak, Fabian; Bucher, Heiner C.; Kettelhack, Christoph; von Strauss und Torney, Marco
Abstract: Background: In 2013 Swiss health authorities implemented annual hospital caseload requirements (CR) for five areas of visceral surgery. We assess the impact of the implementation of CR on indication for surgery in esophageal, pancreatic and rectal cancer. Materials and methods: Retrospective analysis of national registry data of all inpatient admissions between January 1st, 2005 and December 31st, 2015. Primary end-point was the age-adjusted resection rate for esophageal, pancreatic and rectal cancer among patients with at least one cancer-specific hospitalization per year. We calculated age-adjusted rate ratios for period effects before and after implementation of CR and odds ratios (OR) based on a generalized estimation equation. A relative increase of 5% in age-adjusted relative risk was set a priori as relevant from a health policy perspective. Results: Age-adjusted resection rates before and after the implementation of CR were 0.12 and 0.13 (Relative Risk [RR] 1.08; 95%-Confidence Interval [CI] 0.85–1.36) in esophageal cancer, 0.22 and 0.26 (RR 1.17; 95%-CI 0.85–1.58) in pancreatic cancer and 0.38 and 0.43 (RR 1.14; 95%-CI 0.99–1.30) in rectal cancer. In adjusted models OR for resection after the implementation of CR were 1.40 (95%-CI 1.24–1.58) in esophageal cancer, 1.05 (95%-CI 0.96–1.15) in pancreatic cancer and 0.92 (95%-CI 0.87–0.97) in rectal cancer. Conclusion: Implementation of CR was associated with an increase of resection rates above the a priori set margins in all resections groups. In adjusted models, odds for resection were significantly higher for esophageal cancer, while they remained unchanged for pancreatic and decreased for rectal cancer.